Konsep ilmu, teknologi, dan masyarakat dalam IPS - Jadidah, Ines Tasya; Sartika, Sri Dewi; Putri, Suciani; Maharani, Nabila; Sari, Tri Adha Mayang (CV. Kurnia Grup, 2023)
The purpose of this article is to know and understand the basic concepts of social studies, the objectives of social studies education and its relationship with science, technology and society. The ITM learning process is interdisciplinary or multidisciplinary. This means that in the teaching and learning process in social studies classes, students should be invited, coached and encouraged to study or solve problems or topics, looking at them from various scientific disciplines. In this way, several concepts of science, technology and society can contribute to the main mission of IPS, especially in preparing Indonesian citizens who can see science and know a lot about science, technology and society.